2018
DOI: 10.1037/emo0000358
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-color associations in the context of the face.

Abstract: Facial expressions of emotion contain important information that is perceived and used by observers to understand others' emotional state. While there has been considerable research into perceptions of facial musculature and emotion, less work has been conducted to understand perceptions of facial coloration and emotion. The current research examined emotion-color associations in the context of the face. Across four experiments, participants were asked to manipulate the color of face, or shape, stimuli along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 56 publications
4
51
0
Order By: Relevance
“…Some studies also reported that emotional facial expressions could be associated with specific colours, and thus, we are likely to imagine facial expressions with particular colours. For instance, participants were more likely to relate a happy face with colours such as yellow, a sad face with blue, and an angry face with red . Sutton and Altarriba examined 160 emotional words with both positive and negative meanings, and interestingly, the majority of participants tended to associate colours with specific emotional words .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies also reported that emotional facial expressions could be associated with specific colours, and thus, we are likely to imagine facial expressions with particular colours. For instance, participants were more likely to relate a happy face with colours such as yellow, a sad face with blue, and an angry face with red . Sutton and Altarriba examined 160 emotional words with both positive and negative meanings, and interestingly, the majority of participants tended to associate colours with specific emotional words .…”
Section: Discussionmentioning
confidence: 99%
“…In these graphs, bars indicate the colour of each stimulus: white bar for red, gray bar for yellow, and black-dotted bar for blue happy face with colours such as yellow, a sad face with blue, and an angry face with red. [36][37][38] Sutton and Altarriba examined 160 emotional words with both positive and negative meanings, and interestingly, the majority of participants tended to associate colours with specific emotional words. 38 Children aged 7 to 8 years old also seemed to categorize specific colours into either happy or unhappy emotions, although gender differences in categorization were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that color stimuli are associated with both objects (concrete meanings) and concepts (abstract meanings) before they influence more downstream psychological processes, such as attention and preference. To some extent, abstract meanings might be determined by concrete meanings, such as some abstract color‐emotion associations might be developed from concrete facial color‐emotion co‐occurrences . For example, when one sees a man in a red shirt, the color red can be associated with blood from a fight, implying aggression and facilitating competition .…”
Section: Discussionmentioning
confidence: 99%